(3GdLGeY Hjf GdYde hGdYed GdfGaYs - (3HOjY GdReGf CHh GdYR CHh HcQ ESeGYjd Hf GdQRGQ GdLRQj, GHf GdQRGR GdLRQj,J (B602 (3g` s ((3eMehO bGSe Hf eMeO Hf bGSe Hf Ydj s)
(3ChdgG (B:s
(3hHYO aEfj JUaMJ ef cJH GdoeJbOejf hCYeGd GdeJCNQjf CSHGH GdMjd aj GdMQcGJ GdoeTHgI s
(3BNQgG (B:s
(3PcQ cKjQ eeG GNJQYJg ef GdCYeGd hZhGeV GdCTcGd hGdMeO ddg QH GdYGdejf hGdUdGI hGdSdGe Ydi SjOfG eMeO hBdg hUMHg CLeYjf s
(3fSNI NGeSIs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B364s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdUfGYI hGdCWYeIs